Molecular basis of artifacts in the detection of telomerase activity and a modified primer for a more robust 'TRAP' assay. - Krupp, G (1997)
Human somatic cells have essentially no telomerase activity. Telomerase is linked to tumor genesis and is a valuable marker for malignant growth. Extreme paucity of the enzyme neccessitated development of a PCR-based assay, 'telomeric repeat amplification protocol' (TRAP). Unfortunately, this method is not without difficulties.Amplification products are not related to the size of the amplified telomerase products. Furthermore, false positive results can occur, and careful control of reaction conditions is crucial. We analyzed in detail the molecular basis of artifacts. Based on these data, reverse PCR primer was changed and both problems in the TRAP assay were eliminated.